Proton pump inhibitors and peptic ulcer management: Antioxidant mechanisms - Alfahad, Mohanad; Jasim, Mahmood H M; Qazzaz, Mohannad E; Alassaf, Fawaz A; Abed, Mohammed N (Journal of Drug Delivery and Therapeutics, 2021)
Peptic ulcer (P.U.) is the gastrointestinal tract’s most frequent disorder affecting mainly the stomach and duodenum. Surgical intervention, ingested materials and microbial infections may trigger inflammation that further predispose to oxidative stress. Proton pump inhibitors (PPIs) are group of compounds established for suppressions of gastric acid secretions profoundly and permanently over a reasonably long period of time. Oxidative stress has been shown to be involved in the pathophysiology of various diseases and disorders, including P.U. Particularly when H. pylori infection accompanies it. In addition to the colonization of this microorganism, gastric mucosa may be subjected to extreme oxidative stress with large levels of inflammatory cell aggregation, which may eventually predispose to the disorder. PPIs exert several effects other than gastric acid suppression that can be used to treat Helicobacter pylori infections, disorders of the respiratory tract, viral infections, and other conditions related to dysfunction of endothelium by activating endogenous antioxidant protection and reducing the release of cytokine. Recent therapeutic protocols have recommended PPIs as gastro-protective compounds not only because of their acid suppression properties, but also because of their potent antioxidant and anti-inflammatory properties. Keywords: Proton Pump Inhibitors, Peptic Ulcer, Oxidative Stress, H. pylori